Deciphering the canonical blockade of activated Hageman factor (FXIIa) by benzamidine in the coagulation cascade: A thorough dynamical perspective. (21st July 2019) - Salifu, Elliasu Y.; Agoni, Clement; Olotu, Fisayo A.; Dokurugu, Yussif M.; Soliman, Mahmoud E. S.
Abstract: The experimental inhibitory potency of benzamidine (BEN) paved way for further design and development of inhibitors that target β‐FXIIa. Structural dynamics of the loops and catalytic residues that encompass the binding pocket of β‐FXIIa and all serine proteases are crucial to their overall activity. Employing molecular dynamics and post‐MD analysis, this study sorts to unravel the structural and molecular events that accompany the inhibitory activity of BEN on human β‐FXIIa upon selective non‐covalent binding. Analysis of conformational dynamics of crucial loops revealed prominent alterations of the original conformational posture of FXIIa, evidenced by increased flexibility, decreased compactness, and an increased exposure to solvent upon binding of BEN, which could have in turn interfered with the essential roles of these loops in enhancing their procoagulation interactions with biological substrates and cofactors, altogether resulting in the consequential inactivation of FXIIa. A sustained interaction of the catalytic triad residues and key residues of the autolysis loop impeded their roles in catalysis which equally enhanced the inhibitory potency of BEN toward β‐FXIIa evidenced by a favorable binding. Findings provide essential structural and molecular insights that could facilitate the structure‐based design of novel antithrombotic compounds with enhanced inhibitory activities and low therapeutic risk. Abstract : The conformational dynamics of the crucial loops (autolysis loop and activation loop) and the catalytic triads based on the interaction between activated human β‐FXIIa and benzamidine toward a consequential inactivation of β‐FXIIa.